PENGARUH PENGETAHUAN, SANKSI, PELAYANAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KECAMATAN MEDAN TUNTUNGAN - Reza Radhi Anshari (Fakultas Ekonomi Universitas Samudra, 2021)
This research aimed to find out the effect of tax knowledge, tax penalties, tax services and taxpayers’ awareness on taxpayers’ obligation in paying Land and Building Tax (PBB) in Kecamatan Medan Tuntungan. The samples in this reseach were 100 individual taxpayers registered in the region of Kecamatan Tuntungan. Data analysis technique was multiple linear regression analysy. The result of the reseach showed that tax services and taxpayers’ awareness had significant effect on taxpayers’ obligation. Meanwahile tax knowledge and tax penalties had no significant effect on taxpayers compliance.